Span of Supervision and Repercussions of Envy: The Moderating Role of Meaningful Work - Tariq, Hafiz Muhammad Burhan; Mahmood, Asif; Ahmad, Ayyaz; Khan, Maria; Murtaza, Shah Ali; Ali, Asif Arshad; Molnár, Edina (Frontiers in Psychology, 2022)
Though the current research stream has provided some risk factors for envy at the workplace, little is still known about the drivers and consequences of envy. Based on Vecchio’s theory, this study investigates the ripple effect of the span of supervision on envy. Moreover, it sheds light on the moderating role of meaningful work in their relationship. The data comprising sample size 439 were collected from confrères of four fast food companies listed on the Stock Exchange of Pakistan. Partial Least Square Structural Equation Modeling (PLS-SEM) technique was implemented through SmartPLS 3.3.2 to analyze the measurement and structural relationships. The results demonstrate that a narrow span of supervision will increase work engagement, and reduce instigated incivility via decreasing envy and resource depletion in sequence. Moreover, meaningful work would help regulate the inimical stream of dénouement of envy. Theoretical and practical implications, along with the limitations and future directions, have also been discussed.